Human-induced asynchronous sedimentary records between the north and south of the Changjiang distal mud belt since 2005 CE. (5th November 2021) - Yang, Yang; Xu, Min; Jia, Jianjun; Gao, Jianhua; Zhao, Yifei; Zhou, Liang; Wang, Ya Ping
Abstract: Growing evidence has suggested that human activities could cause significant changes in marine sedimentation processes. The spatio-temporal response of sedimentary environment to human activities, however, remains unclear. Here, we present new evidence of sedimentary changes in the East China Sea over the past three decades (i.e., 1984–2016 CE) by using the mean grain size of sensitive components and geochemical parameters (i.e., Si/Ti and Fe/Al) from two sedimentary records from the Zhejiang-Fujian mud belt (ZFMB). Comparison with a compilation of published data shows that natural climate oscillations were the dominant factors that controlled the sedimentation processes before 2005 CE. Variations in the mean grain size of sensitive components over the ZFMB were mainly controlled by the East Asian Winter Monsoon before 2005 CE. The Si/Ti and Fe/Al ratios in the northern and southern of the ZFMB before 2005 CE were controlled by the Pacific Decadal Oscillation/Kuroshio Current and the East Asian Summer Monsoon, respectively. However, our synthesis shows a significant shift in the sedimentation processes between the north and south of the ZFMB since 2005 CE, i.e., after acceleration of the human imprint on sedimentation (e.g., dam construction). The mean grain size of sensitive components and the Si/Ti and Fe/Al records in the north and south of the ZFMB since 2005 CE are mainly controlled by human activities (e.g., human-induced catchment changes in the Changjiang River) and natural climate oscillations (e.g., the East Asian Winter Monsoon and Pacific Decadal Oscillation/Kuroshio Current), respectively. Our study reveals a human-induced asynchronous sedimentary signal in the East China Sea since 2005 CE, and may be applicable to river-dominated marginal seas worldwide during the human-impacted period, providing new evidence to better characterize the Anthropocene epoch. Highlights: Natural climate oscillations control the sedimentation processes of the Zhejiang-Fujian mud belt before 2005 CE. Asynchronous sedimentation processes exist between the north and south of the Zhejiang-Fujian mud belt since 2005 CE. Human activities cause this asynchronous sedimentary response in space since that time.